2014
DOI: 10.1111/nph.12792
|View full text |Cite
|
Sign up to set email alerts
|

Can frequent precipitation moderate the impact of drought on peatmoss carbon uptake in northern peatlands?

Abstract: SummaryNorthern peatlands represent a large global carbon store that can potentially be destabilized by summer water table drawdown. Precipitation can moderate the negative impacts of water table drawdown by rewetting peatmoss (Sphagnum spp.), the ecosystem's key species. Yet, the frequency of such rewetting required for it to be effective remains unknown. We experimentally assessed the importance of precipitation frequency for Sphagnum water supply and carbon uptake during a stepwise decrease in water tables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 62 publications
4
90
2
Order By: Relevance
“…S1). Indeed, previous studies have shown that inter-annual variations in respiration can be linked to changes in precipitation (Marcolla et al, 2011;Nijp et al, 2014;Ryan et al, 2015;Slot et al, 2014;Yan et al, 2014;Zhou et al, 2007). These results further highlight that soil moisture played an important role in the changes in R eco and the components of R eco that were caused by the experimental warming.…”
Section: Insensitive Response Of R Eco and R S To Warmingsupporting
confidence: 59%
“…S1). Indeed, previous studies have shown that inter-annual variations in respiration can be linked to changes in precipitation (Marcolla et al, 2011;Nijp et al, 2014;Ryan et al, 2015;Slot et al, 2014;Yan et al, 2014;Zhou et al, 2007). These results further highlight that soil moisture played an important role in the changes in R eco and the components of R eco that were caused by the experimental warming.…”
Section: Insensitive Response Of R Eco and R S To Warmingsupporting
confidence: 59%
“…Moreover, site 1 featured the abundant S. magellanicum (another ombrotrophic to weakly minerotrophic hummock species; Laine et al, 2011), site 2 featured the abundant S. angustifolium (tolerating ombrotrophic to minerotrophic conditions; Laine et al, 2011), and site 3 featured the abundant S. girgensohnii, a minerotrophic hollow species (Laine et al, 2011). The two most abundant Sphagnum species at site 4 were S. fuscum (mostly on hummocks but also in hollows, an ombrotrophic species; Laine et al, 2011), with a great ability to recover from desiccation (Nijp et al, 2014), and again the minerotrophic hollow species S. girgensohhnii. See Table 1 for a detailed overview of the vegetation at the sites and see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonality in respiration rates in our study is following the monthly Ta patterns, however CO 2 emission strongly depended on peat moisture. Nijp et al (2014) presented the opinion that in many situations warming does not increase R ECO because of the water access limitation. Our results seem to be in contradiction to this statement since the CO 2 emission in 2014 was higher (0.2 μmol…”
Section: High Yearly and Seasonal Variation Of R Ecomentioning
confidence: 99%